Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Technical Assistance Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations of the IMF mission regarding compilation of Government Finance Statistics in Bosnia and Herzegovina as per the Government Finance Statistics Manual 2014 and the European System of National and Regional Accounts 2010. On the compilation of Excessive Deficit Procedure (EDP) tables, the mission assisted the Central Bank of Bosnia and Herzegovina with the completion of derivation tables for net lending / net borrowing of the budgetary governments of the Federation of Bosnia and Herzegovina and the Republic of Srpska. The mission also recommended implementing a coding system for statistical adjustments to the source data; applying the superdividend test; and further implementing derivation tables for the compilation of EDP tables.